Dramaturgia Oleksandra Irwancia: adaptacja posttotalitarnej rzeczywistości - Derewecka, Anna (Acta Polono-Ruthenica, 2008)
In this article some chosen dramas of O. Irvanets are analyzed in the context of the creative work of BuBaBists, who, sneering at tautological consciousness and language, affect the change of the codes of national culture and violate the pristine position of literature -logos that programmes national and cultural being. The author notices that traditional concept of time and space, dynamics of action, dramatic conflict and the structure of the character in the plays of Irvanets are transformed with the aim of making an attempt of new artistic dialogue with modern audience. Present in dramas of Irvanets questions about the essence of nation, political being, about the identity of the society of the transitional period depicted from the character’s point of view - a puppet, the caricature of the average postsoviet citizen, have the ambivalent significance. In author’s opinion, Irvanets imitating the automatism of speaking and totalitarian mirror image of language is ironic about the hero’s persuit of oblivion in the comfort of counterfeit world, where image dominates the object and reality. The dramatist, exposing the mechanisms of the commonplace kitsch, that creates the illusion of artificially maintained unity, which gives the feeling of satisfaction and beauty, demythologizes Ukrainian posttotalitarian awareness that is dominated by the gender divisions.